Review of the round herrings of the genus Etrumeus (Clupeidae: Dussumieriinae) of Africa, with descriptions of two new species - Di Battista, Joseph; Randall, J.; Bowen, B. (2012)
A review of the round herrings of the genus Etrumeus from Africa is presented based on morphological and molecular evidence. Etrumeus golanii is described from the northern Red Sea (and also an immigrant to the Mediterranean), and Etrumeus wongratanai is described from the east coast of Africa, from Durban to northeastern Somalia. The species described herein are characterized by reciprocally monophyletic mitochondrial DNA cytochrome b sequences (d = 3.30%), indicating a long period of separation (ca. 1.65 million years). Etrumeus golanii and E. wongratanai were formerly identified as the northwestern Atlantic species of the genus, E. sadina (regarded as a senior synonym of E. teres), from which they are modally distinct in having 47-51 and 43-47 gill-rakers respectively, versus 48-54. E. wongratanai and E. whiteheadi from South Africa are sympatric near Durban, but are distinct based on mtDNA sequence divergence (d = 19.0%), the number of vertebrae (52 or 53 for E. wongratanai versus 50), and gill-raker count (51-56 for E. whiteheadi versus 43-47).